COVID-19 infection prevalence in pediatric population: Etiology, clinical presentation, and outcome - Fahad Alsohime; Mohamad-Hani Temsah; Abdulrahman M. Al-Nemri; Ali M. Somily; Sarah Al-Subaie (Elsevier, 2020)
Novel COVID-19 infections caused major morbidity and mortality globally in the adult age group. Likewise, SARS-COV-2 infections in children are highly risky in the selected patient population. We performed a focused literature search of published reports from December 1, 2019, till August 20, 2020. The aim was to explore the etiology, clinical presentations, and outcome of pediatric COVID-19 patients. Viral respiratory infections are associated with high societal costs for children. In addition, children with asymptomatic SARS-COV-2 infections can be a source of COVID-19 spread to parents and caregivers. The major reported risk factors for pediatric COVID-19 cases were close contact with a SARS-COV-2 positive family member, a history of travel, and/or living in endemic areas. Children with COVID-19 who required ICU care had various comorbidities, such as malignancy. As the pandemic evolved, multiple cases of multisystem inflammatory syndrome in children and adolescents temporarily related to covid-19 (MIS-C) were reported. A unique population is neonates born to COVID-19 affected mothers, as there is an urgent need to optimize their management and outcome during this rapidly evolving pandemic. The early identification of SARS-COV-2 infection in infants and children has important direct management effects in these children and public health implications because of the effects on disease transmission control measures.